2022
DOI: 10.1111/famp.12775
|View full text |Cite
|
Sign up to set email alerts
|

Love in the time of COVID‐19: A systematic mapping review of empirical research on romantic relationships one year into the COVID‐19 pandemic

Abstract: The COVID‐19 pandemic has affected nearly every area of daily life, including romantic relationships. With the pandemic still ongoing, this study reviewed the existing scholarly literature to document the status of empirical research on how COVID‐19 has affected couples during its first year. Studies were identified through searching five databases as well as sources of gray literature. Overall, 42 studies on committed romantic relationships during the first year of the pandemic were identified. The mapping pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 122 publications
(166 reference statements)
1
32
0
Order By: Relevance
“…Moreover, results from the International Sexual Health and Reproductive (I-SHARE; [10]) survey suggested that people who had a steady relationship starting before COVID-19 showed an increased in sexual satisfaction. This finding is not surprising, as it could be speculated that having a steady relationship may be associated with more positive communication, less fear of transmitting COVID-19, and a reduction in mental health issues related to the pandemic and social restrictions [2,11].…”
Section: Psychological and Sexual Effects Of The Pandemicsmentioning
confidence: 81%
See 4 more Smart Citations
“…Moreover, results from the International Sexual Health and Reproductive (I-SHARE; [10]) survey suggested that people who had a steady relationship starting before COVID-19 showed an increased in sexual satisfaction. This finding is not surprising, as it could be speculated that having a steady relationship may be associated with more positive communication, less fear of transmitting COVID-19, and a reduction in mental health issues related to the pandemic and social restrictions [2,11].…”
Section: Psychological and Sexual Effects Of The Pandemicsmentioning
confidence: 81%
“…The increase in psychological stress and the social restrictions have also had an impact on individuals' sexual functioning [1]. Accordingly, a recent systematic review [2], showed that most of individuals have experienced a decrease in overall sexual functioning, which was related to many factors including fear of transmitting COVID-19 and the increase in depression, anxiety, and stress. For example, a research conducted on the Italian population [3] showed that couples experienced negative mood associated with the discrepancy between their high sexual desire and the scarcer possibilities of actually engaging in sexual activities.…”
Section: Psychological and Sexual Effects Of The Pandemicsmentioning
confidence: 99%
See 3 more Smart Citations